Pelatihan Kewirausahaan Digital Facebook Sayuran Kangkung Di Bengkulu Tengah - Rusminita, Esi; Hanila, Siti (Jurnal Gotong Royong, 2024)
in increasing interest in entrepreneurship for the community. starting a business through technological advances and being ready to face business opportunities in the digital era This Community Service Activity is entitled "Digital Entrepreneurship Training Facebook Vegetables Kangkung in Central Bengkulu which involves several communities. This activity is carried out with the aim of providing knowledge and training about Digital Entrepreneurship where the development of digital technology opens up new opportunities for entrepreneurship and society. However, it is lacking. skills and even education which makes there are still many obstacles when starting a business. This activity is filled with explanations so that they can have an understanding of digital entrepreneurship.The results of this activity show that digital entrepreneurship training is very effective.